Flexible Power Regulation and Limitation of Voltage Source Inverters under Unbalanced Grid Faults - Peng Cheng; Kongyuan Li; Chao Wu; Jing Ma; Limin Jia (CES Transactions on Electrical Machines and Systems, 2022)
This paper develops a flexible power regulation and limitation strategy of voltage source inverters (VSIs) under unbalanced grid faults. When the classical power theory is used under unbalanced grid faults, the power oscillations and current distortions are inevitable. In the proposed strategy, the extended power theory is introduced to compute the power feedbacks together with the classical power theory. Based on the combination of the classical and extended power theory, the proposed strategy can achieve the sinusoidal current provision and the flexible regulation between three common targets, i.e., constant active power, balanced current, and constant reactive power. Meanwhile, the proposed strategy is associated with a power limiter, which is capable to keep the currents under the pre-defined threshold and to compute the maximum apparent power for better utilization of the inverter capacity. With this power limiter, the rated inverter capacity is fully used for both the active and reactive power provisions under unbalanced grid faults. Using the proposed power regulation and limitation, the VSI can avoid overcurrent tripping and flexibly regulate its power under unbalanced grid faults. All the conclusions are verified by the real-time hardware-in-loop tests.